PENYU DAN WARGA PULAU SIAU - Evander E Aiba; Billly Th. Wagey; Ping A Angmalisang; Anneke V. Loho; Deslie Kumampung; Farnis B Boneka (Sam Ratulangi University, 2020)
The study of the perception residents of the Siau island regarding the existence of sea turtles was carried out from June to December 2018. The survey method and direct observation were applied in data collection. The data collected then were analyzed descriptively. The results showed that 88 % of the residents are well acquainted with the life of sea turtles followed by 80 % of the residents knew of the sea turtles’ status as the protected animals through government regulations and international conventions. However, the proportion of residents involved in violating regulations are quite worrying to the survival of sea turtles. For it was found that 29% of the residents were catching sea turtles, 20 % were selling sea turtle meat and eggs, and 82 % were consuming sea turtle meat and eggs. Thefefore, law enforcement and conservation education are absolutely neccesary for the sustainability of sea turtles in North Sulawesi Indonesia. Keywords: Sea turtle, Siau Island, resident’s perception, law enforment. Conservation education AbstrakTelaah presepsi warga pulau Siau terhadap keberadaan penyu laut telah dilaksanakan pada Juni-Desember 2018. Metode survey dan observasi langsung diaplikasikan dalam pengumpulan data, dan data dianalisa secara deskripsif. Hasil menunjukkan bahwa warga mengenal dengan baik kehidupan penyu (88%) dan statusnya sebagai satwa yang dilindungi melalui regulasi pemerintah dan konvensi Internasional (80%). Namun proporsi warga yang terlibat dalam pelanggaran terhadap peraturan cukup mengkuartirkan akan keberlangsungan hidup penyu, yakni menangkap penyu (29%), menjual daging dan telur penyu (28%), mengkonsumsi daging dan telur penyu (82%). Penegakkan hukum dan edukasi diperlukan demi kelestarian penyu di Sulawesi Utara dan Indonesia pada umumnya.Kata kunci: Penyu laut, Pulau Siau, persepsi warga, penegakan hokum, pendidikan konservasi